2021
DOI: 10.2147/iprp.s244709
|View full text |Cite
|
Sign up to set email alerts
|

Considering the Potential Benefits of Over-the-Counter Naloxone

Abstract: Since 1999, annual opioid-related overdose (ORO) mortality has increased more than six-fold. In response to this crisis, the US Department of Health and Human Services outlined a 5-point strategy to reduce ORO mortality which included the widespread distribution of naloxone, an opioid antagonist that can rapidly reverse an opioid overdose. Increased distribution has been facilitated by the implementation of naloxone access laws in each US state aimed at increasing community access to naloxone. While these laws… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…In addition, as has been reported in the literature, many of the participants in the present study identified cost as a perceived barrier to naloxone use among PWUO, in particular (Bowles et al, 2020;Davis et al, 2013;Kahn et al, 2020;Khatiwoda et al, 2018;Lankenau et al, 2013;Richert, 2015;Rochester & Graboyes, 2020;Wagner et al, 2014;Walley et al, 2013). To mitigate this issue, policymakers and medical professionals have proposed the re-classification of naloxone as an over-the-counter (OTC) medication (Evoy et al, 2021). Community and treatment programs should also continue to provide no cost naloxone to PWUO and the community to increase access (Rochester & Graboyes, 2020).…”
Section: Discussionmentioning
confidence: 57%
“…In addition, as has been reported in the literature, many of the participants in the present study identified cost as a perceived barrier to naloxone use among PWUO, in particular (Bowles et al, 2020;Davis et al, 2013;Kahn et al, 2020;Khatiwoda et al, 2018;Lankenau et al, 2013;Richert, 2015;Rochester & Graboyes, 2020;Wagner et al, 2014;Walley et al, 2013). To mitigate this issue, policymakers and medical professionals have proposed the re-classification of naloxone as an over-the-counter (OTC) medication (Evoy et al, 2021). Community and treatment programs should also continue to provide no cost naloxone to PWUO and the community to increase access (Rochester & Graboyes, 2020).…”
Section: Discussionmentioning
confidence: 57%
“…Evoy et al 1 are to be commended for their cogent and thorough review of the potential benefits of over-the-counter (OTC) naloxone. Expanding access to this life-saving medication has the potential to reduce opioid overdose mortality and be a net benefit to the community.…”
Section: Dear Editormentioning
confidence: 99%
“…The medication naloxone, often known by the brand name Narcan, is an opioid receptor antagonist that is highly effective at reversing an opioid overdose. Naloxone has been used in hospitals and emergency departments for four decades, and its safety and efficacy are well established [ 1 , 10 - 12 ]. If naloxone is administered before death, even by a layperson, opioid overdose survival approaches 100% [ 1 , 10 ].…”
Section: Introductionmentioning
confidence: 99%